2021
DOI: 10.25105/ber.v21i2.10409
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Investment Decision Analysis

Abstract: In managing finances, each aims to be able to generate income for himself. Investment is one of the individual decisions to increase the assets owned by allocating a certain amount of funds, time, and assets that are considered to generate returns. Millennial investors are the government's main target through financial literacy education that the Financial Services Authority has promoted in encouraging an increase in stock investment by the public. However, many factors influence investors to invest, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
2
1
1
Order By: Relevance
“…Based on the research findings, there is a positive influence between the use Fintech and the decision to invest in cryptocurrency. This study supports previous research findings by Jonathan & Sumani (2021), which indicated that using Fintech plays a role in influencing investment decisions by facilitating financial activities, especially in Fintech investments. The variable of Fintech usage in this study explains the utilization of technology in financial service systems, resulting in new technological service products and business models.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the research findings, there is a positive influence between the use Fintech and the decision to invest in cryptocurrency. This study supports previous research findings by Jonathan & Sumani (2021), which indicated that using Fintech plays a role in influencing investment decisions by facilitating financial activities, especially in Fintech investments. The variable of Fintech usage in this study explains the utilization of technology in financial service systems, resulting in new technological service products and business models.…”
Section: Discussionsupporting
confidence: 92%
“…The use of Financial Technology, as indicated by Lee & Shin (2018), mainly through Robo-advisors, instills confidence in investors. Additionally, Jonathan & Sumani (2021) suggest that Financial Technology positively impacts investment decisions among millennials. However, conflicting research exists.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of this study are in the opposite direction to research (Junianto et al, 2020), (Jonathan & Sumani, 2021) explaining that financial technology has a positive value on investment decisions. Research according to (Pinem, 2021) explains that financial technology has a significant effect on Investation decision.…”
Section: H2 : Financial Technology Has No Effect On Individual Invest...contrasting
confidence: 96%
“…The level of financial literacy was found to be influenced by income level, education level, and workplace activity. Research according to (Jonathan & Sumani, 2021) states that financial literacy has a positive effect on investment decisions. (Kusumahadi & Utami, 2022) the variable that influences investment decisions is financial literacy with a positive and significant relationship.…”
Section: H1 : Financial Literacy Has a Positive Effect On Individual ...mentioning
confidence: 99%
“…Penelitian sebelumnya menemukan bahwa pengetahuan keuangan dapat memprediksi dengan baik perilaku investasi generasi milenial (Kunaifi, 2019). Penelitian lainnya menemukan bahwa pengetahuan keuangan dan teknologi keuangan berpengaruh dalam keputusan investasi kaum milenial (Jonathan, 2021). Milenial lebih tertarik dalam berinvestasi dengan aset kripto dimana milenial pria lebih memiliki pengetahuan mengenai keuangan dibandingkan milenial wanita (Patil, 2019).…”
unclassified